Analysis of the Impact of Post-Expansion of Pangandaran Regency in Improving Community Welfare in Pangandaran Regency - Edvard Alif Adz Dzikry; Asep Nurwanda; Regi Refian Garis (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This research is motivated by an analysis of the post-expansion impact of Pangandaran Regency on improving community welfare in Pangandaran Regency. However, current problems persist. The purpose of this study is to determine the post-expansion impact of Pangandaran Regency on improving community welfare in Pangandaran Regency. The method used in this study is descriptive analysis. Seven informants were interviewed. Data collection techniques included literature review, fieldwork (observation and interviews), and documentation. The author used qualitative data analysis techniques through processing interview and observation data to draw conclusions that can answer the research questions. Based on the research results, it is known that: the expansion of Pangandaran Regency has provided broader institutional space for local governments to formulate development policies and programs focused on local needs. However, in its implementation, disparities persist between regions, both in terms of access to education, health, social facilities, and economic opportunities. The education aspect has not shown significant improvement. Access to schools, affordability, and the quality of teaching staff remain issues, particularly in villages far from service centers. Similarly, in the health sector, the availability of community health centers and medical personnel has increased, but is not yet fully equitable and accessible to all levels of society. Similarly, in the social sector, community involvement in social activities is still limited by a lack of facilities and infrastructure supporting social interaction. Meanwhile, in the economic sector, the development of leading sectors such as tourism and MSMEs has shown potential, but has not been accompanied by equitable distribution of benefits and expanded access to economic resources for communities across the region. Unemployment and poverty rates continue to indicate that improvements in welfare are not evenly distributed. Keywords: Analysis, Post-Impact, Regional Expansion of Pangandaran Regency, Community Welfare